SYNTHESIS, CRYSTAL STRUCTURE AND LUMINESCENT PROPERTY OF A DINUCLEAR Tb(II) COMPLEX WITH HOMOPHTHALIC ACID AND 2,2’-BIPYRIDYL - LI-HUA WANG (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A novel dinuclear Tb(III) complex, [Tb(bpy)2L2] (bpy = 2,2’-bipyridine, H2L = homophthalic acid), has been synthesized and characterized by elemental analysis and single-crystal X-ray diffraction. The Tb(III) complex is monoclinic, space group P21/c with a = 9.368(2) Å, b = 15.948(4) Å, c = 12.216(3) Å, β = 103.023(4)º, V= 1778.2(7) Å3, Z = 2, Dc = 1.910 mg·m-3, μ = 4.011 mm-1, F(000) = 996, and final R1 = 0.0602, ωR2 = 0.2192. The result shows that the Tb(III) center is seven-coordination with a N2O5 distorted pengonal bipyramidal geometry. The luminescent property of Tb(III) complex was investigated.